Freshwater ecosystem services in mining regions: Modelling options for policy development support - Mercado-Garcia D. (2018)
This research was funded by Cienciactiva, an initiative of CONCYTEC (grant contract No. 002-2016-FONDECYT, and by a VLIR-TEAM programme ZEIN2013PR395: ‘Impact on surface water resources and aquatic biodiversity by opencast mining activities in Cajamarca, Peru’.